Expression Profiling and Functional Analysis of Circular RNAs in Inner Mongolian Cashmere Goat Hair Follicles - Shang, Fangzheng; Wang, Yu; Ma, Rong; Di, Zhengyang; Wu, Zhihong; Hai, Erhan; Rong, Youjun; Pan, Jianfeng; Liang, Lili; Wang, Zhiying; Wang, Ruijun; Liu, Zhihong; et al. (Frontiers in Genetics, 2021)
Background: Inner Mongolian cashmere goats have hair of excellent quality and high economic value, and the skin hair follicle traits of cashmere goats have a direct and important effect on cashmere yield and quality.Circular RNA has been studied in a variety of tissues and cells. Result: In this study, high-throughput sequencing was used to obtain the expression profiles of circRNA in the hair follicles of Inner Mongolian cashmere goats at different embryonic stages (45, 55 , 65 and 75 days). A total of 21784 circRNAs were identified. At the same time, the differentially expressed circRNA in the six control groups formed in the four stages were: d75vsd45,59 up-regulated and 33 down-regulated DE circRNAs; d75vsd55, 61 up-regulated and 102 down-regulated DE circRNAs; d75vsd65, 32 up-regulated and 33 down-regulated DE circRNAs; d65vsd55,67 up-regulated and 169 down-regulated DE circRNAs; d65vsd45, 96 up-regulated and 63 down-regulated DE circRNAs; and d55vsd45, 76 up-regulated and 42 down-regulated DE circRNAs. Six DE circRNA were randomly selected to verify the reliability of the sequencing results by qRT-PCR. Subsequently,the circRNA corresponding host genes were analyzed by GO and the KEGG pathway. The results showed that the biological processes related to hair follicle growth and development enriched by GO mainly included hair follicle morphogenesis, hair follicle maturation and cell development, and the signal pathways related to hair follicle development included the Notch signaling pathway and NF-kappa B signaling pathway.We combined the DE circRNA of d75vsd45 with miRNA and mRNA databases(unpublished) to construct the co-expression network of circRNA-miRNA-mRNA, and formed a total of 102 pairs of circRNA-miRNA and 126 pairs of miRNA-mRNA interactions. The binding relationship of circRNA3236-chi-miR-27b-3p and circRNA3236-chi-miR-16b-3p was further verified by dual-luciferase reporter assays,and the results showed that circRNA3236 and chi-miR-27b-3p,circRNA3236 and chi-miR-16b-3p have a targeted binding relationship. Conclusion: To summarize, we established the expression profile of circRNA in the fetal skin hair follicles of cashmere goats, and found that the host gene of circRNA may be involved in the development of hair follicles of cashmere goats. The co-expression network of circRNA-miRNA-mRNA that DE circRNA was constructed and preliminary verification was carried out.